Optimization of Nuclear Technology as a Sustainable Solution for Clean Water Production - Anaska, Asty; Salsabila, Cindy; Wahyuni, Sri; Said, Sukmawati (Physics Department, Faculty of Mathematics and Natural Sciences, Universitas Negeri Makassar, 2025)
Desalination can improve water quality, reduce water scarcity issues, and enhance both quality of life and economic conditions. Nuclear desalination is considered one of the viable sources for producing clean water, especially in arid or dry regions and coastal areas. Currently, several countries have shown interest in using nuclear energy for seawater desalination. This is because nuclear desalination is feasible and economically viable, as demonstrated by its implementation in various countries. The main advantage of utilizing nuclear technology in desalination is the availability of a large energy source, which enables efficient and sustainable desalination operations even in remote areas, leading to a renewed global interest in nuclear technology.